1997
DOI: 10.1051/forest:19970302
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over effect of gibberellins (GA4/7) and ringing on female flowering in Norway spruce (Picea abies (L) Karst) seedlings

Abstract: Summary -The second year after treatment effect of gibberellins (GA 4/7 ) and ringing on increased female flowering was observed in 13-year-old full-sibs of Norway spruce. This carry-over effect was exhibited independently by GA 4/7 and ringing. GA 4/7 significantly increased and ringing sig-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Staghorn sumac normally does not flower until 4-5 yrs of age. Growth regulators used alone were also effective in promoting precocious flowering in Larix decidua (Hoist 1962) and, combined with girdling, forced flowering in P. abies (Bonnet-Masimbert 1987, Chalupka 1996. Hoekstra & Mergen (1957) significantly increased flowering in 7-yr-old Pinus elliottii seedlings that had no history of flowering, with girdling, wire strangulation, root pruning, and fertilization treatments.…”
Section: Artificially Induced Precocious Floweringmentioning
confidence: 96%
“…Staghorn sumac normally does not flower until 4-5 yrs of age. Growth regulators used alone were also effective in promoting precocious flowering in Larix decidua (Hoist 1962) and, combined with girdling, forced flowering in P. abies (Bonnet-Masimbert 1987, Chalupka 1996. Hoekstra & Mergen (1957) significantly increased flowering in 7-yr-old Pinus elliottii seedlings that had no history of flowering, with girdling, wire strangulation, root pruning, and fertilization treatments.…”
Section: Artificially Induced Precocious Floweringmentioning
confidence: 96%
“…Stimulation of tree flowering can be another factor with a positive influence on cone and seed production within seed orchards. In Poland, the methods of flowering stimulation were described by Chałupka (1985Chałupka ( , 1987Chałupka ( , 1991Chałupka ( , 1997. On the other hand, however, the results then obtained were not definite enough to support fully reliable methodolo-gy for stimulation of Norway spruce flowering.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical and chemical treatments have been used to increase flowering. Hormonal treatments (e.g., gibberellins) have been studied frequently (Bleymüller 1976;Chalupka 1979Chalupka , 1981Chalupka , 1997Dunberg 1980;Luukkanen 1980;Bonnet-Masimbert 1987) and are recommended when reproductive induction and synchrony are fundamental prerequisites for the production of seeds (Kang 2001). Recently, Almqvist (2008) reported that although practical use of GA4/7 in Norway spruce seed orchards does not always have a clear positive effect, the treatment is still a cheap and highly profitable way of increasing the cone production.…”
Section: Genetics Researchmentioning
confidence: 99%